2001
DOI: 10.1002/sia.980
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties and solderability behaviour of nickel–phosphorus and nickel–boron deposited by electroless plating

Abstract: X-ray photoelectron spectroscopy (XPS), scanning Auger microscopy (SAM), atomic force microscopy (AFM) and wetting force measurements have been applied to various nickel deposits prepared by standard electroless plating for probing the origins of solderability behaviour of 'electroless nickel'. By controlling the plating chemicals and plating conditions, three kinds of electroless nickel deposits have been prepared, namely electroless nickel-high phosphorus (EN-HP), electroless nickel-low phosphorus (EN-LP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…5,6 However, still to be understood is the mechanism of interfacial reaction during reflow and information on the interfacial reaction product at the solder joint is still needed. An electronic package is generally subjected to different thermal and mechanical loads during manufacturing, storage, transport and operation.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, still to be understood is the mechanism of interfacial reaction during reflow and information on the interfacial reaction product at the solder joint is still needed. An electronic package is generally subjected to different thermal and mechanical loads during manufacturing, storage, transport and operation.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Especially, Sn-Ag system solder alloys are recognized as the first choice for Pb-free solder. [11][12][13] Copper has been widely used in the under bump metallurgy (UBM) of chip and substrate metallization for chip packaging. However, due to the rapid formation of Cu-Sn intermetallic compound (IMC) at the Sn-based solder/Cu interface during soldering reaction, the reliability of this solder joint has been a serious concern.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that increasing the pH of the Ni-P plating solution increases the nodule size of the Ni-P layer. 10,26,27 However, Chow et al 28 reported that increasing the pH decreased the nodule size of Ni-P. In fact, their plating temperature was 88°C at pH of 4.8 and 44°C at pH of 8.5, Effect of Ni-P Plating Temperature on Growth of Interfacial Intermetallic Compound in Electroless Nickel Immersion Gold/Sn-Ag-Cu Solder Joints thus Chow et al decreased the plating temperature when they increased the pH.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] The P content in the Ni-P layer affects the interfacial IMC thickness, joint strength, and solder wettability. [10][11][12] These properties of the Ni-P layer depend on the Ni-P electroless plating conditions, including temperature, pH, additives, etc. Hence, the effects of these conditions on the properties of the Ni-P layer and the solder joint must be evaluated.…”
Section: Introductionmentioning
confidence: 99%